Pembangkit Listrik Tenaga Hybrid Berbasis Energi Surya dan Energi Angin - Sepdian (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2019)
One of the problems in the field of electrical energy is limited fossil energy resources are the main source of electrical energy producer in Indonesia. To reduce the impact of electricity dependence on the availability of this fossil, it needed a new source of electrical energy that can be renewed. Hybrid power is one source of electrical energy, which is sourced from the light and wind gusts that are environmentally friendly. Due to this hybrid power source of the sun and the wind is, the output voltage of electricity is not stable, because the change according to the circumstances surrounding nature. Batteries are one of the tools that can store electrical energy and can accommodate energy output from the hybrid power source. This research will be discussed rationing system is a hybrid of the capacity of the energy storage system, which includes the relationship between light intensity and the wind blowing against the current and the voltage is raised, and the efficiency increase of the energy storage system.